Blepharoplasty: results of using two techniques in the Ophthalmologic Center from Santiago de Cuba - Marisela Smith Diburnet; Ana Celia Pérez Ruiz; Sonia Cedeño López; Irene Cruz Martínez; Enrique Rodríguez Smith (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: Blepharoplasty produces favorable clinical and cosmetic results in the patients that are suffering from dermatochalasis. Objective: To evaluate the results of the conventional and CO2 laser surgical procedures in these affected patients. Methods: A descriptive, prospective and cross-sectional study of 300 patients with dermatochalasis, assisted in the Oculoplasty Service of "Dr. Juan Bruno Zayas Alfonso"TeachingGeneralHospitalOphthalmologicCenter was carried out inSantiago de Cuba, from January, 2015 to December, 2016. Results: There was a prevalence of the 40 to 59 age group, female sex and  upper lids disorder, without significant differences concerning the surgical techniques that were used; a higher number of complications in  patients operated with a conventional way was observed, with more frequency of bleeding.  In general the patients had a favorable clinical course and those that presented limitations of the upper visual field  recovered without difficulty after the surgical intervention. Conclusions: Blepharoplasty with CO2 laser constitutes a better and more qualified therapeutic option for the correction of dermatochalasis.